ANALISIS PERILAKU NASABAH PEREMPUAN TERHADAP SIMPAN PINJAM KELOMPOK: (Studi Kasus PNM Mekaar Desa Betung Bedarah Timur, Kecamatan Tebo Ilir, Kabupaten Tebo, Provinsi Jambi) - Feni Ayu Astuti; Ahmad Syahrizal; Rohana (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
The world economy is now starting to worry about the people, both the lower, middle and upper classes. So that triggers them to do savings and loans to meet the needs of life. The purpose of this study was: to determine the behavior of female customers in Betung Bedarah Timur Village towards the Savings and Loans of the PNM Mekaar Group. This study used qualitative research methods. Data collection techniques with observation, interviews and documentation. The number of respondents in this study were 50 people. The results of this research are that is misuse of funds by female customers of PNM Mekaar in Betung Bedarah Timur village, the funds disbursed are used for consumptive needs, not productive ones, and there are also coustumers who are categorized as prosperous who participate in making savings and loans at PNM Mekaar. Factors that influence customers to make savings and lons at the Madani National Capital Institution (PNM) Mekaar are internal factors, namely motivation, where they make savings and loans based on something they want to achieve or aim for.